Helicobacter cinaedi bacteremia with cellulitis in a living-donor kidney transplant recipient identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry: a case report. (December 2017) - Katsuma, Ai; Yamamoto, Izumi; Tsuchiya, Yukiko; Kawabe, Mayuko; Yamakawa, Takafumi; Katsumata, Haruki; Mafune, Aki; Nakada, Yasuyuki; Kobayashi, Akimitsu; Koike, Kentaro; Shimizu, Akihiro; Tanno, Yudo; et al.
Abstract Background Helicobacter cinaedi causes bacteremia and cellulitis, mainly in immunocompromised patients. We report a rare case ofH. cinaedi bacteremia with cellulitis in a living-donor kidney transplant recipient identified by matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). Case summary A 54-year-old Asian man with IgA nephropathy underwent living-donor kidney transplantation 14 years previously. He was admitted to our hospital for evaluation of fever and multifocal cellulitis.H. cinaedi was isolated and identified from the patient's blood using matrix-assisted laser desorption ionization time-of-flight mass spectrometry and gyrase subunit B-targeted polymerase chain reaction assays. Matrix-assisted laser desorption ionization time-of-flight mass spectrometry has proven over the years to be a rapid and accurate universal method for the identification of microorganisms. Conclusions The combined use of these detection methods enabled the appropriate administration of 6 weeks of antibiotic therapy. The patient recovered completely, with no recurrence.